2012
DOI: 10.1002/pssb.201100562
|View full text |Cite
|
Sign up to set email alerts
|

Chiral second‐harmonic generation from small organic molecules at surfaces

Abstract: The molecules of life are chiral. Advanced materials for heterogeneous enantioselective catalysis and biomolecular sensing and recognition will need nanoscale chiral structures, and methods of characterizing them. Optical circular dichroism (CD) is the main technique for probing chiral molecules in solution. Amino acids are levorotatory, but CD cannot detect chirality in ultrathin films of these small molecules at surfaces, as the response is too weak. Chiral second-harmonic generation (SHG) from ultrathin lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…As we demonstrated for thin films of 1,1′‐bi‐2‐naphtol on glass, analyzing the polarization of the second harmonic beam generated by the sample can determine the optical activity of thin molecular films with high precision . It was also revealed that, in agreement with theory, the chiroptical effects are enhanced by orders of magnitude for nonlinear processes …”
Section: Spectroscopic Methods To Analyze Model Heterogeneous Asymmetsupporting
confidence: 73%
See 1 more Smart Citation
“…As we demonstrated for thin films of 1,1′‐bi‐2‐naphtol on glass, analyzing the polarization of the second harmonic beam generated by the sample can determine the optical activity of thin molecular films with high precision . It was also revealed that, in agreement with theory, the chiroptical effects are enhanced by orders of magnitude for nonlinear processes …”
Section: Spectroscopic Methods To Analyze Model Heterogeneous Asymmetsupporting
confidence: 73%
“…58 It was also revealed that, in agreement with theory, the chiroptical effects are enhanced by orders of magnitude for nonlinear processes. [150][151][152][153][154] Alternatively, using circularly polarized light for s-SHGS and comparing the efficiency of second harmonic generation for left and right circularly polarized light, the circular dichroism (CD) of the sample can be determined. Doing so, the anisotropy factor of the sample, defined as the difference of the signals for the signals recorded with left and right circularly polarized light divided by the average of the two, can be extracted according to the following equation.…”
Section: Spectroscopic Methods To Analyze Model Heterogeneous Asymmmentioning
confidence: 99%
“…To investigate the origin of the SHG we used a method previously applied to chiral molecular layers. [24][25][26][27][28][29][30] This involves measuring the dependence of the s-or p-polarised components of the SH emission on the orientation of the linearly polarised incident light with respect to the scattering plane (denoted by the angle q). The OA-SHG measurements were performed using a system described in detail elsewhere [31][32][33]41 and which utilises a Nd:YAG pulsed laser (Quanta Ray Coherent Ltd) (8 ns, 1064 nm).…”
Section: Methodsmentioning
confidence: 99%
“…Hence the properties of the substrates can be assumed to be homogeneous and the plane wave based formalism used to describe molecular systems is valid for the metamaterials studied, and the microscopic origins of the SHG response can be determined. [20][21][22][23][24] Optically active second harmonic generation (OA-SHG), utilising a range of measurement methodologies, has been widely used to probe the structure, including chirality, of (bio)molecular materials, [24][25][26][27][28][29][30] and adsorbate-induced chiral perturbations of the electronic structure of achiral metal surfaces. [31][32][33] The non-linear optical activity displayed by chiral metamaterials has been investigated less extensively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation